Implementasi Kurikulum Merdeka oleh Guru SD Penggerak di Bontang Kalimantan Timur - Ramadhan, Rachman; Durrotun Nafisah, Aisyah (Indonesian Journal of Islamic Elementary Education, 2025)
This research is motivated by developing the competencies of mobilizing teachers that are relevant to the needs of the labour market and daily life such as critical thinking skills, interpersonal skills, problem solving skills and adaptability to be able to implement the Merdeka Curriculum in accordance with the existing principles. The purpose of this study is to find out how the driving school teachers and staff understand the Merdeka Curriculum, to find out the extent to which the Merdeka Curriculum is implemented in learning practices in the driving school, and to find out how the readiness of resources in Bontang Mobilizing Elementary School in East Kalimantan supports the effectiveness of the Merdeka Curriculum. The research method used is descriptive quantitative research method with survey type. The results showed that the effectiveness of Merdeka Curriculum by SD Penggerak teachers in Bontang, East Kalimantan was at a high average level with a score of 83.46. The implementation of the Merdeka Curriculum among the teachers of SD Penggerak in Bontang, East Kalimantan must be continuously promoted by the school principal so that the achievement of the Merdeka Curriculum is even more optimal. School principals should continue to provide intensive support and supervision for the implementation of the Merdeka Curriculum so that students' learning outcomes are consistent with the objectives of the Merdeka Curriculum itself.